2022
DOI: 10.3390/molecules27165117
|View full text |Cite
|
Sign up to set email alerts
|

Active Pharmaceutical Ingredient-Ionic Liquids (API-ILs): Nanostructure of the Glassy State Studied by Electron Paramagnetic Resonance Spectroscopy

Abstract: Active Pharmaceutical Ingredient-Ionic Liquids (API-ILs) draw increasing interest as a particular class of ILs that possess unusual physicochemical properties along with simultaneous potentials for pharmaceutical applications. Although nanostructuring phenomena were actively investigated in common ILs, their studies in API-ILs are scarce so far. In this work, using the complex methodology of Electron Paramagnetic Resonance (EPR) and dissolved spin probes, we investigate nanostructuring phenomena in a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 65 publications
3
18
0
Order By: Relevance
“…To observe and investigate structural anomalies in IL glasses, we employed the combination of continuous wave (CW) and pulse EPR techniques, as was used in a series of our previous works [39][40][41][42][43][44][45][46][47]56]. The pulse EPR study relies on the methodology of stochastic molecular librations, previously developed and broadly applied by Dzuba et.al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To observe and investigate structural anomalies in IL glasses, we employed the combination of continuous wave (CW) and pulse EPR techniques, as was used in a series of our previous works [39][40][41][42][43][44][45][46][47]56]. The pulse EPR study relies on the methodology of stochastic molecular librations, previously developed and broadly applied by Dzuba et.al.…”
Section: Methodsmentioning
confidence: 99%
“…A recent series of IL studies using pulse electron paramagnetic resonance (EPR) spectroscopy revealed peculiar molecular dynamics in the glassy state near the glass transition temperature (T g ) [39][40][41][42][43][44][45][46]. Such "structural anomaly" was first found in imidazolium-based ILs, and was later observed for other ILs, phthalates, alkyl alcohols, and alkyl benzenes [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…API-ILs nanostructure can be evaluated in the same manner as for other ILs: via collection of Continuous Wave Electron Paramagnetic Resonance (CW EPR) spectra of the compounds with dissolved N1 and TEMPO–D 18 spin probes. This has been recently shown for API-ILs for the first time, in an elegant study designed to understand interionic arrangement of the API-IL ions, through elucidation of H-bonding between the radicals and IL ions . The most interesting observations were noticed for ibuprofenate-based ILs with 1-alkyl-3-methyl­imidazolium cations with shorter (ethyl), approximately the same (butyl), or longer (hexyl) alkyl substituents than the ibuprofenate anion which has an isobutyl alkyl substituent.…”
Section: Pharmaceutical Purity? Overview Of Current Synthesis and Cha...mentioning
confidence: 99%
“…This has been recently shown for API-ILs for the first time, in an elegant study designed to understand interionic arrangement of the API-IL ions, through elucidation of H-bonding between the radicals and IL ions. 305 The most interesting observations were noticed for ibuprofenate-based ILs with 1-alkyl-3methylimidazolium cations with shorter (ethyl), approximately the same (butyl), or longer (hexyl) alkyl substituents than the ibuprofenate anion which has an isobutyl alkyl substituent. When the cation had a shorter alkyl chain ([1-ethyl-3-methylimidazolium][ibuprofenate]), the micelles around the spin probe were formed by alkyl moieties of the anion, whereas when the cation had longer alkyl substituents ([1-hexyl-3-methylimidazolium][ibuprofenate]) than the radical probe was surrounded by alkyl chains of the cations.…”
Section: Determination Of Ionization and Aggregation To Classify Phar...mentioning
confidence: 99%